The Limpopo Magma‐Rich Transform Margin, South Mozambique – 2: Implications for the Gondwana Breakup. Issue 12 (9th December 2021) - Roche, V.; Leroy, S.; Guillocheau, F.; Revillon, S.; Ruffet, G.; Watremez, L.; d'Acremont, E.; Nonn, C.; Vetel, W.; Despinois, F.
Abstract: The rifted continental margins of Mozambique provide excellent examples of continental passive margins with a significant structural variability associated with magmatism and inheritance. Despite accumulated knowledge, the tectonic structure and nature of the crust beneath the South Mozambique Coastal Plain (SMCP) are still poorly known. This study interprets high‐resolution seismic reflection data paired with data from industry‐drilled wells and proposes a structural model of the Limpopo transform margin in a magma‐rich context. Results indicate that the Limpopo transform margin is characterized by an ocean‐continent transition that links the Beira‐High and Natal valley margin segments and represents the western limit of the continental crust, separating continental volcano‐sedimentary infilled grabens from the oceanic crust domain. These basins result from the emplacement of the Karoo Supergroup during a Permo‐Triassic tectonic event, followed by an Early Jurassic tectonic and magmatic event. This latter led to the establishment of steady‐state seafloor spreading at ca.156 Ma along the SMCP. A Late Jurassic to Early Cretaceous event corresponds to formation of the Limpopo transform fault zone. Which accommodated the SSE‐ward displacement of Antarctica with respect to Africa. We define a new type of margin: the magma‐rich transform margin, characterized by the presence of voluminous magmatic extrusion and intrusion coincident with the formation and evolution of the transform margin. The Limpopo transform fault zone consists of several syn‐transfer and ‐transform faults rather than a single transform fault. The intense magmatic activity was associated primarily with mantle dynamics, which controlled the large‐scale differential subsidence along the transform margin. Key Points: A narrow ocean‐continent transition characterizes the Limpopo magma‐rich transform margin A set of major transform faults consistent with a dextral strike‐slip system defines the Limpopo transform fault zone A long‐lived magmatic activity marks the geodynamic evolution of Mozambique margins from early rifting to oceanic seafloor spreading